2015
DOI: 10.1007/978-3-319-22834-1_16
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Prophylactic and Therapeutic EBV Vaccines

Abstract: Over the last century, the development of effective vaccine approaches to treat a number of viral infections has provided the impetus for the continual development of vaccine platforms for other viral infections, including Epstein-Barr virus (EBV). The clinical manifestations associated with EBV infection occur either following primary infection, such as infectious mononucleosis, or following an extended period of latency, primarily the EBV-associated malignancies and potentially including a number of autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…One possible approach to developing such a vaccine would be to target gp350 or other viral proteins [73]. A small trial evaluating a vaccine against EBV showed limited results in MS [74]. Recent advances in vaccination with a focus on genomic vaccines, that are able to deliver multiple proteincoding sequences, could help to advance vaccination studies in MS [75].…”
Section: Vaccinationmentioning
confidence: 99%
“…One possible approach to developing such a vaccine would be to target gp350 or other viral proteins [73]. A small trial evaluating a vaccine against EBV showed limited results in MS [74]. Recent advances in vaccination with a focus on genomic vaccines, that are able to deliver multiple proteincoding sequences, could help to advance vaccination studies in MS [75].…”
Section: Vaccinationmentioning
confidence: 99%
“…Along with the management of HIV individuals and ART program, interventions to reduce cancer risk factors should also be implemented in this population. Cancer prevention measures in PLWHA should include smoking cessation, HBV and HCV treatment, vaccination against HBV and HPV, annual cervical and anal Pap tests and cancer screening according to relevant guidelines 4, 133138 . Furthermore, a better understanding of cancer risk attributable to specific factors in different HIV infected groups is needed to develop strategies in preventing cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative strategy to induce a cell-mediated immunity to control latent-infected cells in persistently infected individuals may have a role in the prevention of EBV-related malignancies and autoimmune disorders. 19 Due to the capability of the virus to establish latent infection in B cells, 14 in those who already have MS, potential therapeutic strategies include B-celldepleting therapies and anti-retroviral drugs. Rituximab, ocrelizumab and ofatumumab are monoclonal antibodies targeting CD20 + B cells which have shown disease-ameliorating effects in clinical trials.…”
Section: Ebvmentioning
confidence: 99%